Trends in the valuation of injury involving the face: an analysis on trial in Rio Grande do Sul, Brazil - Gabriela Cauduro da ROSA; Rosane Pérez BALDASSO; Mário Marques FERNANDES; Fábio DELWING; Rogério Nogueira de OLIVEIRA (Faculdade São Leopoldo Mandic, 2020)
ABSTRACT Introduction Facial injuries may change, considerably, people's quality of life. To measure the damage, the assessment of the bodily harm is required. Objective To analyze jurisprudential characteristics involving the valuation of the damage related to facial trauma, highlighting trends Methods It was analyzed secondary data, which are public domain, of the precedents of the Court of Justice of Rio Grande do Sul State from 2008 to 2016. The sample consisted of 43 lawsuits in cases related to traffic accidents, falls or physicalaggression that affected the face. Results It was found that 86% of authors and defendants of the lawsuits analyzed are male. In 62.7% of cases physical aggression was the form of trauma that caused more injuries and the most common damage was dental fractures with 53.49%. The monetary restitution for moral damages ranged from R$1,500.00 to R$20,340.00, and for aesthetic damage ranged from R$2,000.00 to R$20,000.00. Conclusion The analyzed jurisprudence involving facial trauma allows us to verifythe trend of need and value of the dentist expert to quantify damage involving the maxillofacial complex.